Is coffee a useful source of caffeine preexercise? - Pickering, C.; Grgic, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Caffeine is a well-established ergogenic aid, with its performance-enhancing effects demonstrated across a wide variety of exercise modalities. Athletes tend to frequently consume caffeine as a performance enhancement method in training and competition. There are a number of methods available as a means of consuming caffeine around exercise, including caffeine anhydrous, sports drinks, caffeine carbohydrate gels, and gum. One popular method of caffeine ingestion in nonathletes is coffee, with some evidence suggesting it is also utilized by athletes. In this article, we discuss the research pertaining to the use of coffee as an ergogenic aid, exploring (a) whether caffeinated coffee is ergogenic, (b) whether dose-matched caffeinated coffee provides a performance benefit similar in magnitude to caffeine anhydrous, and (c) whether decaffeinated coffee consumption affects the ergogenic effects of a subsequent isolated caffeine dose. There is limited evidence that caffeinated coffee has the potential to offer ergogenic effects similar in magnitude to caffeine anhydrous; however, this requires further investigation. Coingestion of caffeine with decaffeinated coffee does not seem to limit the ergogenic effects of caffeine. Although caffeinated coffee is potentially ergogenic, its use as a preexercise caffeine ingestion method represents some practical hurdles to athletes, including the consumption of large volumes of liquid and difficulties in quantifying the exact caffeine dose, as differences in coffee type and brewing method may alter caffeine content. The use of caffeinated coffee around exercise has the potential to enhance performance, but athletes and coaches should be mindful of the practical limitations